Effectiveness of a positive psychology intervention in reducing depression in young people - León, Paloma (2023)
This study presents the results of an intervention based on positive psychology. The objective was to reduce the levels of depression in young university students. University students were diagnosed by applying group measurement instruments. Based on the results obtained, participants were selected (n = 3) to carry out a five-session intervention for each case, using positive psychology techniques. They answered instruments (pre and post-intervention) on the Positive and Negative Affect Scale (PANAS) and Depression Inventory. The results revealed favorable changes in the participants at the end of the sessions. After the intervention, there was a decrease in the average levels of depression and negative emotions and an increase in the students' positive emotions, with higher levels than those observed before the intervention. We conclude that intervention with positive psychology techniques can improve the emotional health of university students, reducing their depressive symptoms and increasing their positive emotions.